2022
DOI: 10.1109/access.2022.3173745
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Literature Mapping of User Story Research

Abstract: User stories are a widely used artifact in Agile software development. Currently, only a limited number of secondary studies have reviewed the research on the user story technique. These research reviews focused on specific research topics related to ambiguity of requirements, effort estimation, and the application of Natural Language Processing. To our knowledge, a systematic mapping of all user story research has not been performed. To this end, we study the academic literature to investigate what user stori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 205 publications
0
2
0
Order By: Relevance
“…The main findings of the study identified difficulties in understanding the Agile requirements. Inconsistent understanding of Agile was noticed [36].…”
Section: Related Workmentioning
confidence: 99%
“…The main findings of the study identified difficulties in understanding the Agile requirements. Inconsistent understanding of Agile was noticed [36].…”
Section: Related Workmentioning
confidence: 99%
“…These tasks have the same goal, which is to create an interface allowing the user to log in to the system. However, computational algorithms have difficulty in recognizing different text sentences as the same [47], [48]. Natural Language Processing approaches [49]- [51] have been proposed over the years.…”
Section: A Structured Task Modelmentioning
confidence: 99%